2002
DOI: 10.1080/10903120290937987
|View full text |Cite
|
Sign up to set email alerts
|

C an P Aramedics a Ccurately I Dentify P Atients W Ho D O N Ot R Equire E Mergency D Epartment C Are ?

Abstract: In this urban system, paramedics cannot reliably predict which patients do and do not require ED care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 9 publications
0
50
0
1
Order By: Relevance
“…60,61 In addition, one study aimed to evaluate if paramedics could be helpful in determining if patients required emergency care showed paramedics failed to predict which patients do and do not require ED care. 62 One of the main findings is the lack of RCTs in evaluation of DSTs in prehospital care. It is very surprising that many studies are well conducted but not randomized.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 In addition, one study aimed to evaluate if paramedics could be helpful in determining if patients required emergency care showed paramedics failed to predict which patients do and do not require ED care. 62 One of the main findings is the lack of RCTs in evaluation of DSTs in prehospital care. It is very surprising that many studies are well conducted but not randomized.…”
Section: Discussionmentioning
confidence: 99%
“…12 • Under/over-triage rate 62,63 • Paramedic documented decision compared to patient outcome 62,64 or expert panel decision and reported with sensitivity and specificity 62…”
Section: ;17(5)mentioning
confidence: 99%
“…Other studies have suggested that paramedic assessment of need for transport does not correlate with a physician's decision to admit or order advanced imaging studies. 38,39 Additionally, there may be differences between patients transported by SFFD versus those who choose to be transported by other paramedic companies. Patients that have the resources to call a specific company may represent a group with a higher standard of living and less socioeconomic stressors than the population using standard dispatch services from a 9-1-1 call center.…”
Section: Limitationsmentioning
confidence: 99%